Modified polycarbonate material, preparation method thereof and explosion-proof flame-retardant composite material
Through the preparation of modified polycarbonate materials and combined with the polyvinyl chloride layer, the problems of insufficient impact resistance and flame retardant performance of existing materials in flammable and explosive areas are solved, and composite materials with high light transmittance and explosion-proof flame retardant effects are achieved, which are suitable for visual observation windows in chemical plants and laboratories.
Patent Information
- Application Number
- CN202411970390.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
In the application of existing materials in flammable and explosive areas such as chemical plants and laboratories, the impact resistance and flame retardant properties are insufficient, and the light transmittance is low, which cannot meet the needs of real-time monitoring and visual observation.
Modified polycarbonate materials are used, and the raw materials include 50-70% polycarbonate particles, 8-13% acrylonitrile-butadiene-styrene plastic, 10-25% toughener, 10-20% glass fiber and 0.5-5% metal organic frame material, and are prepared by melt granulation and molding processes, and combined with the polyvinyl chloride layer to form explosion-proof flame-retardant composite materials.
The explosion-proof flame retardant effect and light transmittance of the material are achieved, and can be applied to the preparation of explosion-proof devices with good light transmittance or as a visual observation window for explosion-proof devices, improving safety and operability.
Smart Images

Figure CN119899510A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials, and in particular relates to a modified polycarbonate material and a preparation method thereof, and an explosion-proof and flame-retardant composite material. Background Art
[0002] In recent years, with the significant advancement of chemical research, the chemical industry has experienced rapid growth. However, this has also led to numerous chemical safety issues. Explosions are a frequent occurrence in chemical laboratories and chemical plants, causing serious injuries and significant economic losses. To improve safety during chemical R&D and production, while also enabling real-time monitoring of reactions and ensuring operability, researchers are developing transparent visual observation windows with excellent flame-retardant and explosion-proof properties for use in chemical plants, laboratories, and other flammable and explosive areas.
[0003] Currently, a variety of materials have been applied to this purpose, such as polycarbonate (PC), organic glass (PMMA), and organic-inorganic laminated glass. While these materials offer significantly improved impact resistance compared to traditional window glass, they are still inadequate for use in environments subject to high explosive shock. Furthermore, these materials' poor flame retardancy further hinders their application. Therefore, developing a polymer material or structure that combines impact resistance, flame retardancy, and visual performance is crucial. Summary of the Invention
[0004] The main purpose of the present invention is to provide a modified polycarbonate material and a preparation method thereof and an explosion-proof flame-retardant composite material. The technical problem to be solved is how to provide an explosion-proof flame-retardant material that not only has explosion-proof flame-retardant effects but also has good light transmittance.
[0005] The objectives and technical problems solved by the present invention are achieved by the following technical solutions: A modified polycarbonate material is provided, wherein the raw materials, by weight percentage, include: 50-70% polycarbonate particles, 8-13% acrylonitrile-butadiene-styrene plastic, 10-25% toughening agent, 10-20% glass fiber, and 0.5-5% metal-organic framework material.
[0006] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0007] Preferably, in the aforementioned material, the mass percentage of the polycarbonate particles in the raw material is 60-70%; and the ratio of the total mass of the acrylonitrile-butadiene-styrene plastic and the toughening agent to the mass of the glass fiber is 1.3-2.4:1.
[0008] Preferably, in the aforementioned material, the toughening agent is selected from at least one of bisphenol A diglycidyl ether, chlorinated polyethylene, methyl methacrylate-butadiene-styrene copolymer and styrene-ethylene-butylene-styrene block copolymer.
[0009] Preferably, the aforementioned material, wherein the metal organic framework material is selected from at least one of zinc metal organic framework materials, zirconium metal organic framework materials and aluminum metal organic framework materials.
[0010] The purpose of the present invention and the technical problem solved are also achieved by adopting the following technical solutions. According to a method for preparing a modified polycarbonate material proposed by the present invention, the method comprises the following steps:
[0011] Weigh the raw material components in the following proportions and mix them evenly. The weight percentage of each component is as follows: 50-70% polycarbonate particles, 8-13% acrylonitrile-butadiene-styrene plastic, 13-22% toughening agent, 10-20% glass fiber, and 0.5-5% metal organic framework material.
[0012] The mixed material is melted at 250-300° C., granulated, formed, annealed and cooled.
[0013] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0014] Preferably, the aforementioned preparation method further comprises the following steps:
[0015] Before the mixture is melted, the glass fiber and the metal organic framework material are both pretreated with a silane coupling agent; after the pretreatment, the mass of the silane coupling agent covered on the surface of the glass fiber is 0.5-1.5% of the total mass of the glass fiber, and the mass of the silane coupling agent incorporated into the metal organic framework material after the pretreatment is 2-8% of the total mass of the metal organic framework material.
[0016] The purpose of the present invention and the solution to its technical problems are also achieved by adopting the following technical solutions. According to the present invention, an explosion-proof and flame-retardant composite material is proposed, which comprises:
[0017] Polyvinyl chloride layer;
[0018] A modified polycarbonate layer is provided on a polyvinyl chloride layer; the raw materials of the modified polycarbonate layer include, by mass percentage, 50-70% polycarbonate particles, 8-13% acrylonitrile-butadiene-styrene plastic, 13-22% toughening agent, 10-20% glass fiber, and 0.5-5% metal organic framework material; the thickness ratio of the polyvinyl chloride layer to the modified polycarbonate layer is 1-2:4.
[0019] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0020] Preferably, in the aforementioned composite material, the polyvinyl chloride layer and the modified polycarbonate layer are bonded by an adhesive, and the adhesive raw materials, calculated by mass percentage, include: 20-45% of the total mass of polyol and polyamine, 30-60% of isocyanate, 5-20% of small molecule chain extender, 4-5% of flame retardant, and 0.05-0.5% of catalyst; the mass ratio of the polyol to the polyamine is 1:1-2.
[0021] Preferably, the aforementioned composite material further comprises:
[0022] A first metal heat-conducting layer is provided on a single side of the modified polycarbonate layer, and a first flame-retardant and scratch-resistant coating is provided on the first metal heat-conducting layer; and / or,
[0023] A second metal thermally conductive layer is provided on a single side of the polyvinyl chloride layer, and a second flame-retardant and scratch-resistant coating is provided on the second metal thermally conductive layer; the bonding surface between the polyvinyl chloride layer and the modified polycarbonate layer has no film layer; the metal of the first metal thermally conductive layer and / or the second metal thermally conductive layer is selected from at least one of Cu, Ag, Au and Zn.
[0024] Preferably, in the aforementioned composite material, the thickness of the first and / or second metal heat-conducting layer film is 10-100 nm; the thickness of the first and / or second flame-retardant and scratch-resistant coating film is 3-30 μm.
[0025] By means of the above technical solution, the modified polycarbonate material and its preparation method and the explosion-proof and flame-retardant composite material proposed in the present invention have at least the following advantages:
[0026] 1. The present invention provides a modified polycarbonate material and a preparation method thereof. By modifying polycarbonate, the modified polycarbonate material prepared thereby not only has good explosion-proof and flame-retardant effects, but also has good light transmittance, and can be used to prepare explosion-proof devices with good light transmittance or as visual observation windows for explosion-proof devices.
[0027] 2. The explosion-proof and flame-retardant composite material provided by the present invention is improved in explosion-proof and flame-retardant effect by combining a polyvinyl chloride layer with a modified polycarbonate material prepared by the present invention in proportion, and also has good light transmittance.
[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional view of the explosion-proof and flame-retardant composite material prepared in Example 8;
[0030] Figure 2 This is a photo of the explosion-proof and flame-retardant composite material prepared in Example 8;
[0031] Figure 3 This is a schematic diagram of the structure of the explosion-proof and flame-retardant composite material prepared in Example 10. DETAILED DESCRIPTION
[0032] To further illustrate the technical means and effectiveness of this invention to achieve its intended objectives, the following, in conjunction with the accompanying drawings and preferred embodiments, describes a modified polycarbonate material, its preparation method, and its explosion-proof and flame-retardant composite material. The specific implementation, structure, features, and effectiveness of the modified polycarbonate material are described in detail below.
[0033] The inventors found that the explosion-proof materials in the prior art not only need to be improved in terms of flame retardancy and explosion resistance, but also the explosion-proof devices prepared, such as explosion-proof doors, have poor light transmittance, making it impossible for personnel to observe the situation inside the explosion-proof device through the outside, making it impossible to understand the occurrence of accidents inside the explosion-proof device in real time.
[0034] Based on the above findings, the applicant has developed a modified polycarbonate (PC) material by modifying it. The modified PC material not only has high explosion-proof and flame-retardant properties, but also has high light transmittance. It can be used to prepare visible explosion-proof and flame-retardant devices or as windows for explosion-proof and flame-retardant devices. Personnel can observe the situation inside the device through the PC material in time, and can deal with accidents in time when they occur to improve safety.
[0035] In summary, the present invention proposes a modified polycarbonate material, referred to as "modified PC material", whose raw materials, calculated by mass percentage, include: 50-70% polycarbonate (PC) particles, 8-13% acrylonitrile-butadiene-styrene plastic (ABS), 10-25% toughening agent, 10-20% glass fiber, and 0.5-5% metal organic framework material (MOF).
[0036] In the aforementioned scheme, PC particles serve as a matrix material to provide basic optical and mechanical properties for the modified PC material. The present invention strictly limits the mass percentage of PC particles, so that the prepared modified polycarbonate material has high transmittance and good thermal stability, impact resistance, electrical insulation and other properties.
[0037] In the aforementioned scheme, the addition of ABS helps improve the toughness of the modified PC material and enhances its compatibility with other components, thereby enhancing the explosion-proof performance of the modified PC material. Furthermore, the addition of ABS reduces the molten viscosity of the modified PC material, thereby improving its processability. However, the inventors have discovered that if the ABS content is too high, the material's rigidity and strength, particularly its flexural modulus and tensile strength, will decrease. Furthermore, the material's heat resistance and chemical stability will decrease, leading to lower heat distortion temperature and chemical corrosion resistance after molding. Furthermore, if the ABS content is too high, the light transmittance of the modified PC material will be significantly reduced. If the ABS content is too low, the modified PC may suffer from insufficient toughness, prone to brittle fracture upon impact, poor compatibility between materials, difficulty in processing, and reduced impact resistance. Therefore, the amount of ABS added will affect the processing, molding, optical, and mechanical properties of the modified PC material. The present invention strictly limits the ABS content by weight in the modified PC material to ensure that the resulting modified PC material has enhanced explosion-proof performance and excellent optical and mechanical properties.
[0038] In the aforementioned solution, a toughening agent is also added to the modified PC material to improve its toughness, thereby contributing to its improved impact resistance. The present invention strictly controls its content to achieve its design objectives. Excessive levels of toughening agent may lead to decreased strength, reduced heat resistance, and reduced processing properties in the modified PC material. This is because toughening agents primarily enhance toughness, and they typically have relatively low rigidity, strength, and glass transition temperature. Excessively low levels of toughening agent may result in insufficient toughness, brittle cracking, and decreased impact resistance, thereby impacting the mechanical properties of the modified PC material.
[0039] In the aforementioned embodiments, the toughening agent used in some embodiments is selected from at least one of bisphenol A diglycidyl ether (DGEBA), chlorinated polyethylene (CPE), methyl methacrylate-butadiene-styrene copolymer (MBS), and styrene-ethylene-butylene-styrene block copolymer (SEBS); these toughening agents have good compatibility with the other materials of the present invention, facilitating the preparation of a modified PC material with high strength. Preferably, in other embodiments of the present invention, the toughening agent is MBS or SEBS. Under these conditions, not only does it help increase the toughness and strength of the material, but it also ensures that the modified PC material has a high light transmittance.
[0040] In the aforementioned solution, the glass fiber helps improve the rigidity and strength of the modified PC material, enhancing its mechanical properties and heat resistance. The present invention strictly limits the percentage by weight of glass fiber in the modified PC material to ensure that the resulting modified PC material exhibits superior performance. Excessive glass fiber content may improve material strength but may increase brittleness, making it difficult to process and affecting its appearance. Excessive glass fiber content may fail to effectively enhance the mechanical properties of the modified PC material, defeating the primary purpose of adding glass fiber.
[0041] In the aforementioned scheme, the MOF helps improve the flame retardancy of the modified PC material. The present invention strictly limits the weight percentage of MOF in the modified PC material to ensure that the prepared modified PC material has excellent performance. If the MOF content is too high, problems such as matrix performance degradation (such as increased brittleness and decreased mechanical strength), reduced processing performance, and decreased optical properties may occur. If the MOF content is too low, problems such as insufficient flame retardancy and uneven MOF distribution in the system may occur, further affecting the overall performance of the modified PC material. In some embodiments, the MOF is selected from zinc metal-organic framework materials (Zn-MOF), such as zeolite imidazole framework-8 (ZIF-8); zirconium metal-organic framework materials (Zr-MOF), such as zirconium 1,4-carboxybenzene metal-organic framework materials (UiO-66); and aluminum metal-organic framework materials (Al-MOF), such as 1,4-hydroxyaluminum phthalate organic framework materials (MIL-53). The present invention preferably selects these metal-organic framework materials for good compatibility with other material components to facilitate the preparation of modified PC materials with high strength.
[0042] The modified PC material prepared by the above scheme of the present invention has good explosion-proof and flame-retardant properties and high light transmittance, and is easy to be used in explosion-proof devices or as a visual window of explosion-proof devices, so that personnel can understand the situation inside the device in a timely manner.
[0043] Preferably, in some embodiments, the mass percentage of the polycarbonate particles in the raw materials of the modified polycarbonate material of the present invention is 60-70%; and the mass ratio of the total mass of the acrylonitrile-butadiene-styrene plastic and the toughening agent to the mass of the glass fiber is 1.3-2.4:1. Under these conditions, not only is the modified polycarbonate material guaranteed to have high transmittance, but the ABS and the toughening agent can fully exert the toughening effect to avoid brittle failure of the material; the glass fiber can provide sufficient reinforcement to ensure rigidity and dimensional stability; the synergistic effect of each component enables the material to exhibit higher mechanical properties and processing performance.
[0044] The present invention also provides a method for preparing a modified polycarbonate material, which comprises the following steps:
[0045] 1) Weigh and uniformly mix the raw material components in the following proportions: 50-70% polycarbonate pellets, 8-13% acrylonitrile-butadiene-styrene plastic, 13-22% toughening agent, 10-20% glass fiber, and 0.5-5% metal-organic framework material. In some embodiments, the PC pellets preferably have a particle size of 2-6 mm to facilitate melt processing and molding. In some embodiments, the PC and ABS pellets are dried to remove moisture.
[0046] In some embodiments of the aforementioned solution, in order to increase the bonding effect between the glass fiber and other materials, the glass fiber is preferably pretreated as follows:
[0047] The glass fiber is soaked in a silane coupling agent for pretreatment to form pretreated glass fiber. The mass of the silane coupling agent covering the surface of the pretreated glass fiber is 0.5 to 1.5% of the total mass of the glass fiber. This not only increases the compatibility of the glass fiber with other materials, but also improves the dispersibility and thermal stability of the glass fiber.
[0048] In the aforementioned solution, in other embodiments, the MOF is pretreated to increase the bonding effect of the material, as follows:
[0049] The MOF is pretreated with a silane coupling agent (such as KH-560), wherein the weight of the silane coupling agent incorporated into the MOF is 2-8% of the total weight of the MOF. In other embodiments, the weight of the silane coupling agent incorporated into the MOF is preferably 4-6% of the total weight of the MOF.
[0050] The present invention uses a silane coupling agent to treat glass fiber and MOF material to introduce covalent bonds on their surfaces, thereby improving their bonding ability and interface performance with the matrix material, and is beneficial to improving the thermal stability, mechanical properties or chemical resistance of the modified PC material.
[0051] In the aforementioned scheme, the silane coupling agent used for pretreatment of the glass fiber and MOF is 3-aminopropyltriethoxysilane (KH-550) and (3-epoxypropyloxy)propyltrimethoxysilane (KH-560); preferably, in other embodiments, the silane coupling agent is KH-550. The present invention optimizes the silane coupling agent to improve the adhesion between the glass fiber and MOF and the other components, and also helps to enhance the tensile strength of the modified PC material.
[0052] 2) Melting the above-mentioned mixture at 250-300°C, further granulating, molding, annealing and cooling. This melting temperature condition is based on the premise that the raw materials are completely melted, using the lowest possible melting temperature to uniformly melt and mix the PC material with the remaining components, achieving good compatibility. Through physical and chemical reactions, the components are better combined, which is beneficial to the production of modified PC materials with excellent properties. The present invention does not specifically limit the specific process conditions and steps of granulation, molding, and annealing. It is sufficient to prepare the modified polycarbonate material by granulating, molding, and annealing the melt to room temperature.
[0053] The present invention also provides an explosion-proof and flame-retardant composite material (hereinafter referred to as the "composite material"), comprising:
[0054] Polyvinyl chloride layer (referred to as "PVC layer");
[0055] A modified polycarbonate layer (referred to as "modified PC layer") is disposed on the PVC layer. In some embodiments, the modified PC layer is bonded to the PVC layer by an adhesive. The raw materials of the modified PC layer include, by weight percentage, 50-70% PC particles, 8-13% ABS, 10-25% toughening agent, 10-20% glass fiber, and 0.5-5% MOF. The thickness ratio of the PVC layer to the modified PC layer is 1-2:4.
[0056] In the above-mentioned solution, the PVC layer and the adhesive can be directly purchased on the market or prepared by oneself.
[0057] Among numerous polymer materials, PVC has a high light transmittance (over 80%) and can replace organic glass (PMMA), polycarbonate (PC), and polyethylene terephthalate (PET) in applications with lower light transmittance. Due to the presence of chlorine, PVC possesses the strongest flame retardancy compared to these materials. Among common transparent polymer materials, PC possesses excellent thermal stability and impact resistance, with an impact strength approximately 20 times that of PMMA and PVC. Therefore, it has significant advantages in explosion-proof and impact-resistant properties. The present invention prepares a composite material by combining a PVC layer with a modified PC layer in a proportional manner, which not only improves the material's explosion-proof and flame-retardant properties but also helps enhance the composite material's light transmittance.
[0058] Preferably, in the above solution, the light transmittance of the PVC layer is above 80%, and the oxygen index (LOI) value is 30 to 40. The composite material prepared under such conditions has good light transmittance and better flame retardancy.
[0059] Preferably, in the aforementioned scheme, the adhesive used in some embodiments of the present invention is self-produced. The adhesive raw materials include: 20-45% by weight of a total polyol and polyamine, 30-60% by weight of an isocyanate, 5-20% by weight of a small molecule chain extender, 4-5% by weight of a flame retardant, and 0.05-0.5% by weight of a catalyst; the mass ratio of the polyol to the polyamine is 1:1-2. The use of this adhesive not only enhances the bonding between the PC layer and the PVC layer but also helps improve the flame retardancy of the composite material. This is because the phosphorus groups contained in the adhesive of the present invention have excellent flame retardancy and thermal stability, effectively reducing the spread of flame and the release of toxic gases during pyrolysis. The chemical bonding between the phosphorus groups and amino groups in the adhesive enhances the adhesion of the polyurea, enabling it to form a strong bond with a variety of substrates. The high rigidity and toughness of the polyurea itself give it better impact absorption and structural stability in explosion-proof applications.
[0060] In the aforementioned scheme, some embodiments are further preferred, in which a first metal heat-conducting layer is provided on a single side of the modified PC layer, and a first flame-retardant and scratch-resistant coating is provided on the first metal heat-conducting layer; in other embodiments, a second metal heat-conducting layer is provided on a single side of the PVC layer, and a first flame-retardant and scratch-resistant coating is provided on the second metal heat-conducting layer; and there is no film layer on the bonding surface between the PVC layer and the modified PC layer. The present invention provides a metal protective layer on the modified PC layer and / or the PVC layer to accelerate the heat conduction of the explosion-proof flame-retardant composite material, thereby accelerating the heat dissipation effect of the explosion-proof flame-retardant composite material, and further improving the explosion-proof and flame-retardant effect of the explosion-proof flame-retardant composite material to a certain extent. Furthermore, providing a flame-retardant and scratch-resistant coating on the metal heat-conducting layer not only helps to increase the flame-retardant effect of the composite material described in the present invention, but also protects the metal heat-conducting layer to ensure that the design purpose of the metal heat-conducting layer of the present invention is achieved and maintained.
[0061] In the aforementioned scheme, in some embodiments, the metal of the first and / or second metal thermal conductive layer is selected from at least one of Cu, Ag, Au, and Zn; preferably, the metal of the first and / or second metal thermal conductive layer is selected from Zn and / or Ag, which can ensure that the composite material has a high light transmittance and can also save the investment cost of the product. In order to ensure that the composite material of the present invention has good light transmittance and explosion-proof and flame-retardant properties, some embodiments further preferably have a film thickness of 10 to 100 nm. If the film thickness of the metal thermal conductive layer is too thin, the thermal conductivity of the metal thermal conductive layer will be poor, affecting the explosion-proof and flame-retardant effect of the composite material of the present invention; if the film thickness of the metal thermal conductive layer is too thick, the stress of the metal thermal conductive layer will be too large, resulting in cracking of the film layer, and the light transmittance of the film layer will also be affected if it is too thick.
[0062] In some embodiments of the aforementioned scheme, the scratch-resistant layer is a conventional scratch-resistant protective layer, such as a silane-based protective layer or a polyurethane-based protective layer. To prevent the flame-retardant and scratch-resistant layer from affecting the light transmission of the explosion-proof and flame-retardant composite material, other embodiments preferably have a film thickness of 3 to 30 μm. If the flame-retardant and scratch-resistant layer is too thin, it will not provide adequate scratch resistance. If it is too thick, the film may crack.
[0063] The present invention also provides a method for preparing an explosion-proof and flame-retardant composite material, which comprises the following steps:
[0064] 1) Pre-treat the modified PC layer and / or PVC layer. The specific method is as follows:
[0065] First, a metal thermally conductive layer is deposited on the surface of the modified PC layer and / or PVC layer. The present invention does not specifically limit the deposition process; any method capable of depositing a metal thermally conductive layer on the surface of the modified PC layer and / or PVC layer will suffice. In some embodiments, vacuum magnetron sputtering is used to deposit a metal film on the surface of the modified PC layer or PVC layer, forming a first metal thermally conductive layer on the surface of the modified PC layer and / or a second metal thermally conductive layer on the surface of the PVC layer.
[0066] Secondly, a flame retardant and scratch resistant layer is formed on the first metal heat conducting layer and / or the second metal heat conducting layer by using conventional methods such as flow coating or spray coating.
[0067] 2) The pre-treated modified PC layer and the PVC layer are bonded together with an adhesive and cured. The adhesive is not particularly limited, as long as it achieves the bonding purpose of the present invention.
[0068] Preferably, in some embodiments, a self-made adhesive is used to bond the modified PC layer and the PVC layer to increase the bonding strength between the modified PC layer and the PVC layer. The adhesive has certain high temperature resistance and flame retardant properties, which helps to improve the flame retardant properties of the composite material and maintain the stability and explosion resistance of the composite material. The adhesive is specifically as follows:
[0069] The binder raw materials include: in terms of mass percentage, the total mass of polyol and polyamine is 20-45%, 30-60% isocyanate, 5-20% small molecule chain extender, 4-5% flame retardant, and 0.05-0.5% catalyst; the mass ratio of the polyol to the polyamine is 1:1-2.
[0070] In the above scheme, it is further preferred that the preparation of the binder comprises the following steps:
[0071] The binder raw materials are weighed and mixed to form a mixture, and a polyol, a polyamine material, a small molecule chain extender, a phenyl phosphate compound or a derivative is added to a reaction device. The mixture is stirred at 30-40° C. for 8-12 hours to form a uniform mixed liquid; further, isocyanate is added, the temperature is raised to 60-90° C., stirred and kept warm for 0.5-2 hours, and in some embodiments, the temperature is raised at 22-28° C. / h; further, a catalyst is added, and the reaction is continued for 8-12 hours to obtain a polyurea adhesive.
[0072] In the aforementioned scheme, during the preparation of the adhesive, a small molecule chain extender is added to increase the molecular weight of the polyol / polyamine, adjust the hardness, increase the degree of crosslinking, and improve the processing performance; further, the present invention controls the reaction process by limiting the amount of isocyanate and catalyst used, the addition time, and the reaction temperature during the reaction process, thereby avoiding the isocyanate and catalyst being added too early, which causes the reaction to be too intense, resulting in excessive heat generated during the reaction, and causing insufficient reaction of the adhesive, or the generation of agglomerates, weak bonding, and affected flame retardant properties.
[0073] In the aforementioned scheme, in some embodiments, the polyol is selected from at least one of PTMG-1000, PTMG-2000, PTMG-650, PCL-1000, and PCL-2000; the polyamine is selected from at least one of polyetheramine D-2000, M-1000, and T-5000; preferably, in other embodiments, the polyol is PTMG-2000 and / or PCL-1000, and the polyamine is preferably D-2000 and / or T-5000; the purpose of optimizing the polyol or polyamine in the present invention is to ensure that the adhesive prepared by the present invention has good flexibility and adhesion.
[0074] In the aforementioned embodiments, the small molecule chain extender is selected from at least one of ethylenediamine, ethylene glycol methylamine, TMP (trihydroxymethylpropane), and 1,4-BDO (1,4-butanediol) in some embodiments. In other embodiments, the small molecule chain extender is preferably selected from at least one of ethylenediamine, ethylene glycol methylamine, and 1,4-BDO. The preferred small molecule chain extender of the present invention can effectively chain extend the polymer in the binder raw material to a moderate degree, facilitating the preparation of a binder with good flexibility and adhesion. However, TMP is too rigid, and its chain extender has a relatively large effect on the polymer chain extension in the binder raw material, resulting in the prepared binder being too brittle, potentially affecting its explosion-proof effect.
[0075] In the aforementioned scheme, in some embodiments, the isocyanate is selected from at least one of MDI, IPDI, HMDI, and HDI; in other embodiments, the isocyanate is preferably IPDI. The preferred purpose is that the adhesive prepared under such conditions has good weather resistance, heat resistance, and toughness.
[0076] In the aforementioned scheme, in some embodiments, the flame retardant is a phenyl phosphate compound or derivative. Furthermore, the phenyl phosphate compound or derivative is selected from at least one of triphenyl phosphate (TPP), diphenyl phosphate (DBP), tris(chloromethyl) phosphate (TCEP), and tris(2-ethylhexadecyl) phosphate (TEP). These flame retardants are compatible with other components in the binder raw materials, which helps to improve the bonding effect of the binder. In other embodiments, the phenyl phosphate compound or derivative is triphenyl phosphate. The preferred purpose is that the triphenyl phosphate material has good flame retardant effect and thermal stability, the prepared binder has good flame retardant effect and thermal stability, and the binder bonds the PVC layer and the modified PC layer, resulting in a composite material with better flame retardant and explosion-proof properties.
[0077] In some embodiments of the aforementioned scheme, the catalyst is selected from at least one of organotin catalysts such as dibutyltin laurate, diphenyltin diethylamide, and dibutyltin oxide. In other embodiments, the catalyst is preferably dibutyltin laurate. Using this catalyst can better control the reaction process, resulting in a more complete and uniform reaction and good bonding performance of the prepared adhesive.
[0078] In some embodiments of the aforementioned scheme, the adhesive prepared in this invention is poured into the interlayer of the modified PC layer and the PVC layer through a grouting lamination method. The mixture is cured at a curing temperature of 50-80°C for 1-3 days to form an explosion-proof and flame-retardant composite material. Under these conditions, the modified PC layer and the PVC layer have a strong bond, and the resulting explosion-proof and flame-retardant composite material has a better flame-retardant effect and stronger bonding strength than conventional adhesives.
[0079] The explosion-proof flame-retardant composite material prepared by the above scheme of the present invention has good explosion-proof flame-retardant effect and high light transmittance. The explosion-proof device prepared using the explosion-proof composite material or the visualization window of the explosion-proof device can facilitate personnel to observe the situation inside the explosion-proof device.
[0080] The modified PC material or explosion-proof flame-retardant composite material provided by the aforementioned solution of the present invention is applied in the fields of laboratory equipment manufacturing and construction.
[0081] The present invention will be further described below with reference to specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by those skilled in the art based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0082] Unless otherwise specified, the materials and reagents mentioned below are commercially available products familiar to those skilled in the art. Unless otherwise specified, the methods described are all well-known methods in the art. Unless otherwise defined, technical or scientific terms used shall have the same meanings as those commonly understood by those skilled in the art.
[0083] Example 1
[0084] This embodiment provides a modified polycarbonate material and a preparation method thereof, as follows:
[0085] 1) Raw material preparation:
[0086] Weigh the raw materials. The contents of each component in the raw materials are as follows:
[0087] 64% PC particles, 9% ABS, 13% MBS, 11% glass fiber, 3% ZIF-8.
[0088] The PC particles used in this embodiment have a particle size of 4 mm.
[0089] Glass fiber pretreatment:
[0090] The glass fiber was immersed in KH-550 until the mass of KH-550 covering the surface of the glass fiber was 0.5% of the mass of the glass fiber.
[0091] ZIF-8 pretreatment:
[0092] ZIF-8 was immersed in KH-560, and finally the mass of KH-560 covering the surface of ZIF-8 was 3% of the total mass of ZIF-8.
[0093] 2) The pretreated raw materials were mixed by a twin-screw extruder, then melted at 280° C., pelletized, injection molded, and cooled.
[0094] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy. The testing methods are as follows:
[0095] Transmittance: Tested in accordance with GB / T 2680-2021.
[0096] Haze test: Test according to GB / T 2410-2008.
[0097] Impact strength test: Test according to ISO179.
[0098] Flame retardant performance test: Limiting oxygen index (LOI): tested according to GJB 2406.2-2009; flame retardant grade: tested according to UL94-2009.
[0099] The test indicators are shown in Table 1.
[0100] Example 2
[0101] This embodiment provides a modified polycarbonate material and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, with the following differences:
[0102] 1) The content of each component in the raw materials is as follows:
[0103] 50% PC particles, 13% ABS, 20% MBS, 12% glass fiber, 5% ZIF-8.
[0104] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1. The test results are shown in Table 1.
[0105] Example 3
[0106] This embodiment provides a modified polycarbonate material and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, with the following differences:
[0107] 1) The content of each component in the raw materials is as follows:
[0108] Weigh the raw materials. The contents of each component in the raw materials are as follows:
[0109] 68% PC particles, 8% ABS, 10% SEBS, 13.5% glass fiber, 0.5% UiO-66.
[0110] The PC particles used in this embodiment have a particle size of 6 mm.
[0111] After the glass fiber is pretreated, the mass of KH-550 covering the surface of the glass fiber is 1% of the mass of the glass fiber.
[0112] After UiO-66 pretreatment, the mass of KH-560 covering the surface of UiO-66 was 5% of the total mass of UiO-66.
[0113] The melting temperature of the raw materials during the melting process is 250°C.
[0114] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1. The test results are shown in Table 1.
[0115] Example 4
[0116] This embodiment provides a modified polycarbonate material and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, with the following differences:
[0117] 1) Raw material preparation:
[0118] Weigh the raw materials. The contents of each component in the raw materials are as follows:
[0119] 52% PC particles, 12% ABS, 19% DGEBA, 12% glass fiber, 5% MIL-53.
[0120] The PC particles used in this embodiment have a particle size of 6 mm.
[0121] After the glass fiber is pretreated, the mass of KH-560 covering the surface of the glass fiber is 1% of the mass of the glass fiber.
[0122] After MIL-53 pretreatment, the mass of KH-560 covering the surface of MIL-53 is 5% of the total mass of MIL-53.
[0123] The melting temperature of the raw materials during the melting process is 300°C.
[0124] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1. The test results are shown in Table 1.
[0125] Example 5
[0126] This embodiment provides a modified polycarbonate material and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, with the following differences:
[0127] 1) The content of each component in the raw materials is as follows:
[0128] 61.1% PC particles, 8% ABS, 10% MBS, 15.9% glass fiber, 5% ZIF-8.
[0129] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1. The test results are shown in Table 1.
[0130] Example 6
[0131] This embodiment provides a modified polycarbonate material and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, with the following differences:
[0132] 1) The content of each component in the raw materials is as follows:
[0133] 60% PC particles, 13% ABS, 13% MBS, 11% glass fiber, 3% ZIF-8.
[0134] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1. The test results are shown in Table 1.
[0135] Example 7
[0136] This embodiment provides a modified polycarbonate material and a preparation method thereof. The process and steps of this embodiment are basically the same as those of Example 1, with the following differences:
[0137] 1) The content of each component in the raw materials is as follows:
[0138] 60% PC particles, 13% ABS, 14% MBS, 10% glass fiber, 3% ZIF-8.
[0139] The modified polycarbonate material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1. The test results are shown in Table 1.
[0140] Example 8
[0141] This embodiment provides an explosion-proof and flame-retardant composite material and a preparation method thereof, as follows:
[0142] Prepare materials: Take a 4 mm PVC sheet, a 7 mm modified polycarbonate sheet prepared in Example 1 (referred to as "modified PC sheet"), and a 3M polyurethane adhesive as the adhesive.
[0143] The PVC sheet and the modified PC sheet are bonded by grouting and laminating, and then cured at 70°C and cooled.
[0144] The cross-sectional view and the actual photograph of the explosion-proof flame-retardant composite material prepared in this embodiment are shown in FIG. Figure 1 and Figure 2 ;in, Figure 1 11 is a PVC sheet, 12 is a gelling material, and 13 is a modified PC sheet.
[0145] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 1.
[0146] The results of various test indicators are shown in Table 2.
[0147] Example 9
[0148] The difference between this embodiment and embodiment 8 is that:
[0149] Before the PVC sheet and the modified PC sheet are bonded together, a layer of Cu metal film is sputtered on one side of the modified PC sheet by vacuum magnetron sputtering, and the film thickness is 30 nm.
[0150] Then, an organic silicon scratch-resistant layer is prepared on the surface of the metal film layer by spraying, and the film layer thickness is 10 μm.
[0151] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0152] Example 10
[0153] The difference between this embodiment and embodiment 9 is that:
[0154] Before gluing the PVC sheet to the modified PC sheet, a Zn metal film with a thickness of 20 nm was plated on one side of each of the modified PC sheet and the PVC sheet. The plating method was the same as in Example 6.
[0155] Then, an organic silicone scratch-resistant layer was prepared on the surface of the metal film layer of the PVC plate and the modified PC plate. The film layer had a thickness of 10 μm and the preparation method was the same as in Example 9.
[0156] The structural diagram of the composite material prepared in this embodiment is shown in the attached Figure 3 As shown, Figure 1 In the figure, 1 is the second flame retardant and scratch resistant coating; 2 is the second metal heat conductive layer; 3 is the PVC layer; 4 is the adhesive layer; 5 is the modified PC layer; 6 is the first metal heat conductive layer; 7 is the first flame retardant and scratch resistant coating.
[0157] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 9. The results of various test indicators are shown in Table 2.
[0158] Example 11
[0159] The difference between this embodiment and embodiment 9 is that:
[0160] Before the PVC sheet and the modified PC sheet are bonded together, a layer of Ag metal film is plated on one side of the PVC sheet. The film thickness is 20 nm. The plating method is the same as that in Example 6.
[0161] Then, a scratch-resistant layer is plated on the surface of the metal film layer of the PVC plate. The thickness of the plated scratch-resistant layer is 10 μm. The preparation method is the same as that of Example 9.
[0162] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 9. The results of various test indicators are shown in Table 2.
[0163] Example 12
[0164] The difference between this embodiment and embodiment 8 is that the adhesive in this embodiment is a homemade adhesive, and the specific preparation method is as follows:
[0165] Weigh the adhesive raw materials, add PTMG-2000, D-2000, ethylenediamine, and triphenyl phosphate into a reactor, and stir at 30°C for 10 hours to form a uniform mixed solution; further, add IPDI to the mixed solution, raise the temperature to 80°C at 25°C / h, and continue stirring to react for 1 hour; further, add dibutyltin laurate to the reaction solution, and continue the reaction for 10 hours to obtain a polyurea adhesive.
[0166] The binder raw materials include, by mass percentage:
[0167] 20% PTMG-2000, 20.7% D-2000, 15% ethylenediamine, 4% triphenyl phosphate, 0.3% dibutyltin laurate, 40% IPDI.
[0168] The adhesive prepared in this example was poured into the interlayer of the modified PC board and the PVC board by grouting lamination, and cured at a curing temperature of 60° C. for 2 days to form an explosion-proof and flame-retardant composite material.
[0169] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0170] Example 13
[0171] The difference between this embodiment and embodiment 8 is that:
[0172] Weigh the adhesive raw materials, and add PTMG-1000, M-1000, TMP, and diphenyl phosphate into a reactor, and stir at 35°C for 8 hours to form a uniform mixed solution; further, add IPDI to the mixed solution, raise the temperature to 60°C at 22°C / h, and continue stirring to react for 2 hours; further, add diphenyltin diacetamide to the reaction solution, and continue to react for 8 hours to obtain a polyurea adhesive.
[0173] The binder raw materials include, by mass percentage:
[0174] 15.5% PTMG-1000, 24% M-1000, 20% TMP, 5% triphenyl phosphate, 0.5% diphenyltin diethylamide, 35% IPDI.
[0175] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0176] Example 14
[0177] The difference between this embodiment and embodiment 8 is that:
[0178] Weigh the adhesive raw materials, add PCL-1000, T-5000, ethylene glycol methylamine, and triphenyl phosphate into a reactor, and stir at 30°C for 12 hours to form a uniform mixed solution; further, add HMDI to the mixed solution, raise the temperature to 90°C at 28°C / h, and continue stirring to react for 0.5 hours; further, add dibutyltin oxide to the reaction solution, and continue the reaction for 12 hours to obtain a polyurea adhesive.
[0179] The binder raw materials, measured by mass percentage, include:
[0180] 18.95% PCL-1000, 23% T-5000, 10% ethylene glycol methylamine, 3% triphenyl phosphate, 0.05% dibutyltin oxide, 45% HMDI.
[0181] The adhesive prepared in this example was poured into the interlayer of the modified PC sheet and the PVC sheet by grouting and laminating, and cured for 3 days at a curing temperature of 70° C. to form an explosion-proof and flame-retardant composite material.
[0182] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0183] Example 15
[0184] The difference between this embodiment and Example 8 is that the composite material of this embodiment includes a 7 mm thick PVC sheet and a 12 mm thick modified PC sheet prepared in Example 1.
[0185] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0186] Example 16
[0187] The difference between this embodiment and Example 8 is that the composite material of this embodiment includes a 4 mm thick PVC sheet and a 12 mm thick modified PC sheet prepared in Example 1.
[0188] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0189] Example 17
[0190] The difference between this embodiment and embodiment 8 is that the modified PC board is prepared according to embodiment 2.
[0191] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0192] Example 18
[0193] The difference between this embodiment and embodiment 8 is that the modified PC board is prepared according to embodiment 3.
[0194] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0195] Example 19
[0196] The difference between this embodiment and embodiment 8 is that PMMA sheets are used instead of PVC sheets to form a composite material of PMMA sheets and modified PC sheets.
[0197] The explosion-proof flame-retardant composite material prepared in this example was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of various test indicators are shown in Table 2.
[0198] Comparative Example 1
[0199] In this comparative example, a PVC sheet with a thickness of 20 mm was tested for transmittance, haze, impact strength, and flame retardancy using the same testing methods as in Example 8. The results of each test index are shown in Table 2.
[0200] Table 1 Test results of various indicators of Examples 1-7
[0201]
[0202] Table 2 Test results of various indicators of Examples 8-19 and Comparative Examples
[0203]
[0204] Combined with Examples 1 to 7, Table 1 and Appendix Figure 2 It can be seen that the modified polycarbonate material provided by the present invention has good impact resistance and flame retardancy, high light transmittance and low haze. The light transmittance of the modified polycarbonate material is greater than 70%; the haze is less than 9%; and the impact strength is 60 to 90 kJ / m 2 ; Limiting oxygen index>28%, flame retardant grade at least V-0.
[0205] Analysis of Examples 1-7 reveals that when the mass percentage of polycarbonate particles in the modified polycarbonate material raw material is 60-70%; and the mass ratio of the combined mass of the acrylonitrile-butadiene-styrene plastic and the toughening agent to the glass fiber is 1.3-2.4:1, the resulting modified PC material exhibits improved impact resistance. Furthermore, the applicant's research indicates that when the mass ratio of the combined mass of ABS and the toughening agent to the glass fiber is less than 1.3:1, the impact strength decreases significantly, the material is prone to cracking, its rigidity decreases, and its dimensional stability is also poor.
[0206] In conjunction with Examples 8-19, Figure 1-3 As can be seen from the comparative examples, the explosion-proof and flame-retardant composite material claimed in the present invention has a light transmittance greater than 60%, a haze less than 10%, and an impact strength of 75 to 115 kJ / m 2 The limiting oxygen index is greater than 30%, and the flame retardancy grade reaches at least V-0. It is worth noting that the photos of the explosion-proof flame-retardant composite material prepared in Example 8 of the present invention show that when the explosion-proof flame-retardant composite material prepared in Example 8 of the present invention is used as a window material, personnel can clearly observe the internal conditions. This shows that the explosion-proof flame-retardant composite material provided by the present invention not only significantly improves the explosion-proof flame-retardant performance, but also has good light transmittance.
[0207] Comparing Examples 9-11 with other examples, it can be seen that by adopting the technical solution of the present invention, a metal thermal conductive layer is added to the explosion-proof and flame-retardant composite material. Although the transmittance of the composite material decreases, this solution can increase the explosion-proof and flame-retardant effect of the explosion-proof and flame-retardant material by accelerating heat dissipation, and further strictly controlling the type of thermal conductive layer film system and the thickness of the film layer not only helps to avoid the influence of the film layer on the transmittance of the composite material, but also can optimize the thermal conductivity rate.
[0208] Comparing Examples 12-14 with other examples, it can be seen that the adhesive material prepared by the present invention not only increases the bonding effect between PC sheets and PVC sheets and improves the impact strength of the composite material, but also helps to improve the flame retardant properties of the explosion-proof flame retardant composite material. This is because: the flame retardancy and thermal stability of the phosphorus group can effectively reduce the spread of flame and the release of toxic gases during pyrolysis; the chemical combination of the phosphorus group and the amino group enhances the bonding force of the polyurea, enabling it to form a strong bond with a variety of substrates; the high rigidity and toughness of the polyurea itself give it better impact absorption capacity and structural stability in explosion-proof applications.
[0209] Comparing Example 19 with Example 8, it can be seen that after PMMA replaces PC, the light transmittance increases, the haze decreases, and the limiting oxygen index decreases.
[0210] The technical features in the claims and / or the specification of the present invention may be combined, and the manner of combination is not limited to the combination obtained by reference in the claims. The technical solutions obtained by combining the technical features in the claims and / or the specification are also within the scope of protection of the present invention.
[0211] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiment based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A modified polycarbonate material, characterized in that: The raw materials include, by mass percentage, 50-70% of polycarbonate particles, 8-13% of acrylonitrile-butadiene-styrene plastics, 10-25% of toughening agent, 10-20% of glass fiber, and 0.5-5% of metal organic framework material.
2. The material according to claim 1, characterized in that The mass percentage of the polycarbonate particles in the raw material is 60-70%; and the ratio of the total mass of the acrylonitrile-butadiene-styrene plastic and the toughening agent to the mass of the glass fiber is 1.3-2.4:
1.
3. The material according to claim 1, characterized in that The toughening agent is selected from at least one of bisphenol A diglycidyl ether, chlorinated polyethylene, methyl methacrylate-butadiene-styrene copolymer and styrene-ethylene-butylene-styrene block copolymer.
4. The material according to any one of claims 1 to 3, characterized in that The metal organic framework material is selected from at least one of a zinc metal organic framework material, a zirconium metal organic framework material and an aluminum metal organic framework material.
5. A method for preparing a modified polycarbonate material, characterized in that: It includes the following steps: Weigh the raw material components according to the following proportions and mix them evenly, and the mass percentage of each component is as follows: 50-70% polycarbonate particles, 8-13% acrylonitrile-butadiene-styrene plastic, 13-22% toughening agent, 10-20% glass fiber, and 0.5-5% metal organic framework material; The mixed material is melted at 250-300°C, and then granulated, formed, annealed and cooled.
6. The method according to claim 5, characterized in that It also includes the following steps: Before the mixture is melted, the glass fiber and the metal organic framework material are both pretreated with a silane coupling agent; after the pretreatment, the mass of the silane coupling agent covered on the surface of the glass fiber is 0.5-1.5% of the total mass of the glass fiber, and the mass of the silane coupling agent incorporated into the metal organic framework material after the pretreatment is 2-8% of the total mass of the metal organic framework material.
7. An explosion-proof and flame-retardant composite material, characterized in that: It includes: Polyvinyl chloride layer; Modified polycarbonate layer; provided on a polyvinyl chloride layer; The raw materials of the modified polycarbonate layer include, by mass percentage, 50-70% polycarbonate particles, 8-13% acrylonitrile-butadiene-styrene plastics, 13-22% toughening agents, 10-20% glass fibers, and 0.5-5% metal organic framework materials; the thickness ratio of the polyvinyl chloride layer to the modified polycarbonate layer is 1-2:
4.
8. The composite material according to claim 7, characterized in that The polyvinyl chloride layer and the modified polycarbonate layer are bonded by an adhesive, and the adhesive raw materials include, by weight percentage, 20-45% of the total weight of polyol and polyamine, 30-60% of isocyanate, 5-20% of small molecule chain extender, 4-5% of flame retardant, and 0.05-0.5% of catalyst; the mass ratio of the polyol to the polyamine is 1:1-2.
9. The composite material according to claim 7 or 8, characterized in that: It also includes: A first metal heat-conducting layer is disposed on a single side of the modified polycarbonate layer, and a first flame-retardant and scratch-resistant coating is disposed on the first metal heat-conducting layer; and / or, A second metal thermal conductive layer is arranged on a single side of the polyvinyl chloride layer, and a second flame retardant and scratch resistant coating is arranged on the second metal thermal conductive layer; there is no film layer on the bonding surface of the polyvinyl chloride layer and the modified polycarbonate layer; the metal of the first metal thermal conductive layer and / or the second metal thermal conductive layer is selected from at least one of Cu, Ag, Au and Zn.
10. The composite material according to claim 9, characterized in that The thickness of the first and / or second metal heat-conducting layer film is 10-100 nm; the thickness of the first and / or second flame-retardant and scratch-resistant coating film is 3-30 μm.